Os predicados primitivos ACT e DO na representação lexical dos verbos - Luana Lopes Amaral (2013)
This dissertation aims to study some types of agentive activity verbs in Brazilian Portuguese and two primitive predicates, ACT and DO. These primitive predicates are proposed in the literature for the formulation of predicate decomposition structures that could be used as lexical representation for agentive activity verbs. Our purpose is to investigate which one of these primitive predicates is more adequate for the formulation of representations to the verbs we analyze and also if we need to postulate that both predicates exist in an inventory of primitive predicates. Considering Cançado and Godoys (2011) work, which shows that agentive activity verbs in Brazilian Portuguese do not form a grammatically relevant verb class, we raise the hypothesis that both ACT and DO exist in an inventory of primitive predicates and each one of those predicates is used in the representation of a specific class of agentive activity verbs. We found in our data three different verb classes: verbs like correr run, verbs like escrever write, and verbs of creation. We motivate the classification of the verbs using syntactic and semantic diagnostics. Also using that kind of diagnostics, we conclude that verbs like correr are more adequately represented by a structure with the primitive predicate DO and that verbs like escrever are more adequately represented by a structure with the primitive predicate ACT. The verbs of creation are also more adequately represented by a structure with the primitive predicate ACT, but their representation is different from the one proposed for verbs like escrever. We also show that an apparent transitivity alternation found with verbs of creation (o João escrevia João used to write/o João escreveu uma carta João wrote a letter) is, in fact, the result of a process of polysemy.